Seismic performance of mortarless reinforced masonry walls. (September 2020) - Huang, Liang; Lu, Yiqiu; Yan, Libo; Kasal, Bohumil; Wang, Lu; Zhang, Tongyue
Abstract: Reinforced masonry walls are commonly used as a primary lateral load resisting system in buildings in regions of moderate or high seismicity. Mortarless reinforced masonry (MLRM) walls are constructed using concrete masonry units placed without mortar and then interconnected by concrete grout. The absence of mortar can overcome several issues during the construction of conventional reinforced masonry walls. Previous research mainly focused on mortarless systems using three-dimensional interlocking blocks without vertical reinforcement. In this study, a total of six MLRM walls were constructed and tested under cyclic loadings to investigate their seismic behaviour. Experimental parameters included axial load ratio, shear span ratio, and vertical reinforcement ratio of the walls. Test results showed that the MLRM walls exhibited high stiffness, good deformation capacity, and reasonable energy dissipation capacity. The response of all six walls under cyclic loadings was controlled by 3–4 cracks formed at bed joints between the concrete masonry units, and their failure was dominated by flexure with the occurrence of slight shear sliding. The load-displacement envelope, strength, and energy dissipation of all tested MLRM walls are discussed. Highlights: Novel mortarless reinforced masonry (MLRM) wall is proposed. Six MLRM walls were constructed and tested under cyclic loading. Parameters including axial load ratio, shear span ratio and vertical reinforcement ratio were considered. Seismic performance of MLRMs were evaluated and recommendation was provided.